2004
DOI: 10.1359/jbmr.040907
|View full text |Cite
|
Sign up to set email alerts
|

Decreased BMD and Limb Deformities in Mice Carrying Mutations in Both Lrp5 and Lrp6

Abstract: Humans and mice lacking Lrp5 have low BMD. To evaluate whether Lrp5 and Lrp6 interact genetically to control bone or skeletal development, we created mice carrying mutations in both Lrp5 and the related gene Lrp6. We found that compound mutants had dose-dependent deficits in BMD and limb formation, suggesting functional redundancy between these two genes in bone and limb development.Introduction: Lrp5 and Lrp6 are closely related members of the low density lipoprotein receptor family and are co-receptors for W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
250
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(273 citation statements)
references
References 37 publications
21
250
0
2
Order By: Relevance
“…LRP6 plays an essential role during embryogenesis and the severe developmental defects in Lrp6 −/− mice prevent the study of postnatal bone [53]. However, heterozygous Lrp6 +/− and hypomorphic ringelshwanz Lrp6 mutant mice exhibit delays in ossification and decreased bone mass in adults [11,54]. Recently a human LRP6 mutation was reported in a family with coronary artery disease and osteoporosis, further suggesting that loss of function LRP6 mutations result in low bone mass [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LRP6 plays an essential role during embryogenesis and the severe developmental defects in Lrp6 −/− mice prevent the study of postnatal bone [53]. However, heterozygous Lrp6 +/− and hypomorphic ringelshwanz Lrp6 mutant mice exhibit delays in ossification and decreased bone mass in adults [11,54]. Recently a human LRP6 mutation was reported in a family with coronary artery disease and osteoporosis, further suggesting that loss of function LRP6 mutations result in low bone mass [55].…”
Section: Discussionmentioning
confidence: 99%
“…A transgenic mouse model carrying a human LRP5 high bone mass mutation exhibited significant increases in bone density and mechanical properties [9,10]. Studies have shown that removing one Lrp6 copy from Lrp5 −/− mice increases the osteoporosis severity, suggesting that both LRP5 and LRP6 are critical determinants of bone mass [11].…”
Section: Introductionmentioning
confidence: 99%
“…(44) With regard to other possible molecular interactions for sclerostin, data from in vitro experiments had shown that sclerostin could bind LRP6 and inhibit Wnt signaling, (32)(33)(34) similar to the findings for LRP5. This, coupled with mouse genetic data showing that LRP6 appeared to play a role in achieving and/or maintaining normal bone mass, (45)(46)(47) suggested that sclerostin also might interact with LRP6 in vivo. Recently, it has been reported that sclerostin binds to LRP4, a singletransmembrane protein related to LRP5 and LRP6, and, additionally, that LRP4 is expressed in bone by osteoblasts and osteocytes.…”
mentioning
confidence: 89%
“…Similar to humans, Lrp5 -/-mice have a low bone mass phenotype due to reduced proliferation of precursor cells (Kato et al, 2002), which is enhanced by additional loss of one Lrp6 allele (Holmen et al, 2004). Conversely, mice that overexpress the G171V LRP5 mutant, have a high bone mass phenotype (Babij et al, 2003).…”
Section: Dkk1 and 2 In Bone Formationmentioning
confidence: 99%